Interventions for loneliness in older adults: a systematic review of reviews - Patil, Uday; Braun, Kathryn L. (Frontiers in Public Health, 2024)
Loneliness in older persons is a major risk factor for adverse health outcomes. Before the COVID-19 pandemic led to unprecedented isolation and hampered programs aimed at preventing or reducing loneliness, many interventions were developed and evaluated. However, previous reviews provide limited or conflicting summaries of intervention effectiveness. This systematic review aimed to assess previous review quality and bias, as well as to summarize key findings into an overarching narrative on intervention efficacy. The authors searched nine electronic databases and indices to identify systematic reviews of interventions to reduce loneliness in older people prior to the COVID-19 pandemic; 6,925 records were found initially. Of these, 19 reviews met inclusion criteria; these encompassed 101 unique primary intervention studies that varied in research design, sample size, intervention setting, and measures of loneliness across 21 nations. While 42% of reviews had minimal risk of bias, only 8% of primary studies appraised similarly. Among the 101 unique articles reviewed, 63% of tested interventions were deemed by article author(s) as effective or partially effective. Generally, interventions that included animals, psychological therapies, and skill-building activities were more successful than interventions focused on social facilitation or health promotion. However, interventions that targeted multiple objectives aimed at reducing loneliness (e.g., improving social skills, enhancing social support, increasing social opportunities, and changing maladaptive social cognition) were more effective than single-objective interventions. Future programs should incorporate multiple approaches, and these interventions should be rigorously tested.